Rediseño del sistema de lubricación forzada de un compresor reciprocante de gas natural (2022)
Forced lubrication in a reciprocating compressor that transfers natural gas, consists of injecting oil into the cylinders, with a pressure greater than that of the gas being compressed, in order to lubricate the liner, piston and rings, to thus guaranteeing its integrity and expected useful life. The purpose of the project is to minimize oil consumption for forced lubrication of reciprocating compressor cylinders, given that the annual operating cost exceeds the budget assigned by planning. This is achieved by carrying out a redesign in the lubrication system, which consists of modifying the supply of replacement oil to the engine-compressor group, and thus reducing scheduled engine oil changes by half, achieving annual economic savings of 24 million pesos cop. The proposed redesign also implies the installation of an additional filtration system to remove particles and impurities from the oil, guaranteeing an entry in optimal conditions to the cylinders, making adequate lubrication, avoiding premature damage to the liners and pistons, with which it is expected as an added benefit a longer service life of the lubricated components. The proposal also manages to reduce the negative environmental impact, by reducing emissions of oil degraded by operational use and reducing the risk of lubricators, by minimizing the number of oil changes, which implies handling barrels weighing around 200 kg . Keywords: Lubrication, oil, compressor, reciprocating, natural gas.